2003
DOI: 10.2320/matertrans.44.1926
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Processes for Nanostructure Development in Cu after Severe Cryogenic Rolling Deformation

Abstract: The dynamic grain refinement behavior upon severe plastic deformation has been systematically studied in commercial purity copper that was heavily cold rolled to large deformations at cryogenic temperatures. The low-temperature rolling allows the accumulation of extraordinarily high densities of dislocations in Cu, enabling an investigation of the various dynamic recrystallization phenomena upon further deformation. The eventual steady-state grain sizes achieved, as well as the dynamic recrystallization mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…This process provides severe straining with just 50% total reduction of the original thickness in the final product. Similar to cryogenic rolling [45], the accumulation of large strains and high density of dislocations during ARB without dynamic recrystallization does not induce new high angle boundaries and structure refinement.…”
Section: Spd By Ordinary Forming Operationsmentioning
confidence: 96%
“…This process provides severe straining with just 50% total reduction of the original thickness in the final product. Similar to cryogenic rolling [45], the accumulation of large strains and high density of dislocations during ARB without dynamic recrystallization does not induce new high angle boundaries and structure refinement.…”
Section: Spd By Ordinary Forming Operationsmentioning
confidence: 96%
“…8(a)] formed ultrafine grains with dislocation substructures because a large equivalent drawing strain of 7.2 was introduced by cold-wire drawing. When subsequent draw bending was performed on the wiredrawn specimen, it was observed that the CBD specimens had dislocation substructures inside their grains as shown in 19,20) However, the CBD process in the present study was performed at room temperature, and the temperature of the CuSn wire increased during the CBD process. Therefore, no deformation twins were observed on the wire-drawn specimen and CBD specimens.…”
Section: Microstructure Evaluation Under Stemmentioning
confidence: 76%
“…According to the results presented by ref. [19], a commercial purity Cu (higher than 99.9 wt% purity) was cold rolled at cryogenic temperatures (−150°C-−100°C) up to the strain of 30000%, the recrystallization temperature of deformation microstructure was still higher than 150°C. Hence the possibility of further HPT deformation at LNT to induce the Cu recrystallization temperature down to RT was very small, and the exposure of HPT deformed sample into environmental temperature would not induce abnormal grain growth.…”
Section: Resultsmentioning
confidence: 99%